Improved procedural results after CoreValve implantation with the new AccuTrak delivery system - Chorianopoulos, Emmanuel; Krumsdorf, Ulrike; Pleger, Sven Torsten; Katus, Hugo; Bekeredjian, Raffi (Journal of interventional cardiology, 2012)
Aims of the study: Transcatheter aortic valve implantation (TAVI) has become an established treatment for severe aortic stenosis in patients with unacceptable high-surgical risk. Recently, the new AccuTrak delivery system for improved deliverability of the CoreValve aortic bioprosthesis was launched. It has not yet been shown if the new delivery catheter leads to optimized positioning and improved procedural outcomes. Methods and results: We conducted a retrospective single-center analysis and evaluated 70 consecutive patients (35 with the original delivery catheter and 35 with the new AccuTrak catheter) for anatomic positioning and related outcome parameters like postinterventional aortic regurgitation (AR) and the need for permanent pacemaker insertion, after CoreValve implantation. The use of the AccuTrak delivery catheter resulted in significantly higher positioning of the CoreValve prosthesis in the left ventricular outflow tract (distance from annulus to lower edge of prosthesis 7.0 mm [5.5 to 9.4 mm] for the AccuTrak group vs. 8.8 mm [7.1 to 11.2 mm] for the original system; median [interquartile range]; P = 0.0068). Moreover, the optimized positioning resulted in reduced rates of significant (≥grade 2) AR assessed by postinterventional aortography and echocardiography (P = 0.044 and P = 0.0275, respectively). Despite improved positioning, no differences in the need for permanent pacemaker implantation were observed. Conclusions: Our retrospective analysis indicates improved positioning with reduced postinterventional AR with the new CoreValve AccuTrak delivery system. Whether this may also affect the need for permanent pacemaker insertion or long-term outcome after TAVI needs to be evaluated in larger studies. (J Interven Cardiol 2012;25:174-179)
First published: 09 April 2012
Gesehen am 18.07.2018